Typology and Styles of Educational Leadership and Their Implementation in Educational Institutions - Abdul Hamid; Sofi Inayaturrobbaniah (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
Educational leadership is a critical factor in determining program effectiveness, learning quality, and school culture, yet challenges like low management efficiency and weak educator collaboration persist. This study examines various educational leadership styles, typologies, and their practical implementation within educational institutions. Employing a qualitative library research methodology, data were gathered from diverse scientific literature sources, including books and journal articles, and analyzed using content analysis to understand leadership patterns deeply. The results identify five primary contemporary leadership styles: instructional, transformational, distributional, participatory, and adaptive-integrative. While each style possesses distinct characteristics and focuses, they collectively complement one another to support organizational effectiveness. This study concludes that the success of educational leadership depends heavily on the leader's ability to flexibly integrate these various styles according to institutional contexts and needs. Such strategic integration plays a crucial role in improving learning quality, strengthening professional collaboration, and supporting seamless adaptation to changes within the modern educational landscape.